Evaluation of prognosis and outcome of small bowel obstruction using the acute general emergency surgical severity-small bowel obstruction score - Nath, Hemendra C.; Terang, Benedict; Bhuyan, Rupak; Gogoi, Sufil (International Journal of Research in Medical Sciences, 2022)
Background: Small bowel obstruction (SBO) is a common surgical emergency, associated with significant morbidity and mortality specially if strangulated. There was not much used of scoring system for SBO. The aim of the study was to determine the usefulness of acute general emergency surgical severity (AGESS)-SBO score developed by Patrice Wendlling at Mayo Clinic in 2015 to evaluate the prognosis and outcomes of SBO. Methods: 80 patients age ≥13 years who fulfill the study criteria and admitted in surgery ward, Jorhat Medical College and Hospital, Jorhat between May 2020 to October 2021 were identified. The American association for the surgery of trauma (AAST) anatomic score, physiological score and comorbidity score are added to get AGESS-SBO score. Results: The mean age was 41.2 years and males (77.5%) were more affected. Obstructed external hernia (40%) was the most common cause of SBO. 64 patients (80%) were operated and 16 patients were treated conservatively. Complications were seen in 30 patients and 8 patients (10%) died during hospital stay. The median AGESS-SBO score is 5 (IQR 5-6) for complications and 2 (IQR 1.0-2.5) for no complications (p value of 0.0001). Conclusions: Incidence is more in males and obstructed hernia was the commonest cause. Higher the AGESS-SBO score more the complications and so was morbidity and mortality. A score more than 2 has unfavorable outcome.